2022
DOI: 10.3389/fgene.2022.893832
|View full text |Cite
|
Sign up to set email alerts
|

From the patient to the population: Use of genomics for population screening

Abstract: Genomic medicine is expanding from a focus on diagnosis at the patient level to prevention at the population level given the ongoing under-ascertainment of high-risk and actionable genetic conditions using current strategies, particularly hereditary breast and ovarian cancer (HBOC), Lynch Syndrome (LS) and familial hypercholesterolemia (FH). The availability of large-scale next-generation sequencing strategies and preventive options for these conditions makes it increasingly feasible to screen pre-symptomatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 279 publications
(365 reference statements)
0
4
0
Order By: Relevance
“…Systematically identifying and tracking carriers of pathogenic cancer mutations are critical given the availability of effective prevention and surveillance strategies and the increasing use of genetic and genomic testing (Burn et al 2020 ; Meiser et al 2022). Traditional approaches of identifying individuals at risk for hereditary breast-ovarian cancer or Lynch syndrome include family history, ethnicity, or clinical criteria; however, these approaches miss a substantial number of pathogenic carriers, as high as 50% (Mighton et al 2022 ). Previous research has highlighted the benefits of a dedicated inherited cancer service and registry, such as increasing screening rates, decreasing mortality, and facilitating timely research access (Barrow et al 2013 ; Ghorbanoghli 2018 ; Vasen et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Systematically identifying and tracking carriers of pathogenic cancer mutations are critical given the availability of effective prevention and surveillance strategies and the increasing use of genetic and genomic testing (Burn et al 2020 ; Meiser et al 2022). Traditional approaches of identifying individuals at risk for hereditary breast-ovarian cancer or Lynch syndrome include family history, ethnicity, or clinical criteria; however, these approaches miss a substantial number of pathogenic carriers, as high as 50% (Mighton et al 2022 ). Previous research has highlighted the benefits of a dedicated inherited cancer service and registry, such as increasing screening rates, decreasing mortality, and facilitating timely research access (Barrow et al 2013 ; Ghorbanoghli 2018 ; Vasen et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is crucial to reduce the possibility of detecting relationships that are eventually determined to provide false-positive results. The most crucial features of biomarker improvement and identification to consider in depth include mindful study pattern to minimize any kind of bias, extensive evaluation, validation, and accurate communication of the results [ 48 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Cancer Biomarkersmentioning
confidence: 99%
“…Although HBOC has the strongest support for population screening with evidence demonstrating clinical and cost-effectiveness, Lynch syndrome has preliminary evidence and requires additional data. 31 Universal upfront MGPT not only shows improved diagnostic capabilities, but also cost savings. An analysis comparing standard upfront MGPT versus IHC for all newly diagnosed endometrial cancer demonstrated cost savings of $259 per patient.…”
Section: Population Testing Outside the Setting Of A Specific Phenoty...mentioning
confidence: 99%
“…Although HBOC has the strongest support for population screening with evidence demonstrating clinical and cost-effectiveness, Lynch syndrome has preliminary evidence and requires additional data. 31…”
Section: Population Testing Outside the Setting Of A Specific Phenoty...mentioning
confidence: 99%